Application of AgNWs (at) CdZnS2 (at) Cd, Zn-ZIF-8 core-shell structure in photocatalysis and extraction of uranium from seawater
By controlling AgNWs doping g-CdZnS2, AgNWs@CdZnS2@Cd and Zn-ZIF-8 core-shell structure photocatalytic materials are prepared, which solves the challenge of the existing CdZnS2 photocatalytic materials efficiently catalyze uranyl in seawater, and achieves efficient uranyl reduction capabilities and simple and controllable preparation processes.
Patent Information
- Application Number
- CN202411723083.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
There are still challenges in the efficient catalyzing of uranyl in seawater with existing CdZnS2 photocatalytic materials, and their photocatalytic efficiency is far from meeting the requirements of practical applications.
By controlling AgNWs doping g-CdZnS2, the photocatalytic hydrogen production performance of g-CdZnS2 was improved, and the photocatalytic materials of AgNWs@CdZnS2@Cd and Zn-ZIF-8 core-shell structures were prepared. The material is prepared by AgNWs@ZIF8 as a precursor, combined with urea, and heat treatment and vacuum drying.
The AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials are efficiently increased uranium in seawater, have excellent uranyl reduction capabilities, and are simple in preparation technology, strong controllability and high yield.
Smart Images

Figure CN119549164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photocatalytic material, in particular to a AgNWs@CdZnS2@Cd, Zn-ZIF-8 core-shell structure photocatalytic material and its preparation and application in extracting uranium from seawater. Background Art
[0002] Due to the rapid development of nuclear energy, uranium, as the main component of nuclear fuel, has been released into seawater, causing many hazards. The efficient, low-cost and environmentally friendly reduction of uranyl in seawater has become an urgent issue.
[0003] CdZnS2 (hereinafter referred to as SCZ) is a typical ternary sulfide solid solution composed of cadmium, zinc and sulfur elements. It has the advantages of a wide band gap of 3.6 eV for ZnS and a narrow band gap of 2.4 eV for CdS. It has been widely studied for its flexible band gap and band edge position. CdZnS2 also has the advantages of simple preparation process, strong visible light response, and strong resistance to photocorrosion, and is widely used in the field of photocatalysis. However, due to defects such as fast recombination of photogenerated carriers, slow charge transfer, and photocorrosion under light irradiation, its efficiency is far from meeting the requirements of practical applications. In response to the above factors, some measures have been taken, such as adjusting the morphology and structure of photocatalysts, element doping, introducing co-catalysts, and using sacrificial agents, to meet the requirements of practical applications. Among these measures, more people have studied element doping because it can introduce impurity atoms and change the band structure to significantly improve the photocatalytic activity.
[0004] Due to the introduction of impurity atoms, the impurity bands formed in the bandgap of SCZ and the band structure of SCZ changed. The visible light response was significantly enhanced, and the charge regulation and transport were promoted, which increased the concentration of photogenerated carriers. Tang et al. synthesized a Zn x Cd 1-x Co y S (Enhancing photochemical activity of semiconductor nanoparticles with optically active Ag nanostructures: photochemistry mediated by Ag surface plasmons [J]. The Journal of Physical Chemistry C, 2010, 114 (19): 9173-9177). Co is uniformly distributed around the porous solid solution skeleton using Co-doped ZIF-8 as a precursor. After doping with 0.5% Co, the photocatalytic hydrogen evolution rate of SCZ is further increased to 17.36 mmolh -1 g -1, which is 46.2 times higher than that of undoped SCZ. Compared with undoped SCZ, the flat band potential of the composite photocatalyst after cobalt doping showed a significant upward trend, which is beneficial to carrier separation. In addition, Peng et al. synthesized Bi-doped Cd 0.5 Zn 0.5 S(Remarkable enhancement of photocatalytic hydrogen evolution over Cd 0.5 Zn 0.5 S by bismuth-doping[J].Internationaljournalofhydrogenenergy,2012,37(2):1366-1374). When the Bi doping content is low, the doped ions are located at the surface lattice sites, while when the doping content is high, the ions also enter the bulk lattice sites. When the Bi doping content is 0.10mol%, the photocatalyst shows the highest activity. In addition to doping metal elements in SCZ, some non-metallic elements can also be doped to improve the photocatalytic activity. For example, Ye et al. synthesized P-doped SCZ (P-dopedZn x Cd 1-x S solid solutions as photocatalysts for hydrogen evolution from watersplitting coupled with photocatalytic oxidation of 5-hydroxymethylfurfural[J].Applied Catalysis B:Environmental,2018,233:70-79). In SCZ with abundant S vacancies, interstitial P doping can prolong the lifetime of charge carriers and enhance the generation and separation of photogenerated electron holes. The impurity energy level of S vacancies is a shallow trap state, located between the conduction band and the Fermi level. When the impurity energy level is located near the Fermi level, it can act as an electron trap center and can promote the Fermi level by doping with donor impurities. Although it has been recognized that SCZ has great potential in the fields of environmental protection and renewable energy production, since most reactions need to be carried out in the presence of sacrificial reagents, whether SCZ materials can be efficiently catalyzed in seawater remains challenging. Summary of the invention
[0005] The purpose of the present invention is to provide an AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalysis and seawater uranium extraction application, by controlling the AgNWs doping g-CdZnS2, to improve the photocatalytic hydrogen production performance of g-CdZnS2.
[0006] In order to achieve the above object, the present invention provides a method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials, the method comprising:
[0007] Propylene glycol containing PVP was placed in a bottle and heated in an oil bath with magnetic stirring. Then NaCl was quickly added and stirred continuously, followed by the addition of AgNO3 solution, and the mixed solution was heated with magnetic stirring. The precipitate was collected and washed with acetone and ethanol, respectively, to obtain gray AgNWs. 2-Methylimidazole is dissolved in an organic solvent solution containing an organic amine, and AgNWs is mixed therein, and then added to an organic solvent solution of a cadmium salt and a zinc salt, stirred at room temperature, allowed to stand, and solid-liquid separated to obtain AgNWs@ZIF8; wherein the organic amine is selected from any one of triethylamine, ethylenediamine and n-butylamine; the organic solvent is selected from any one of methanol, ethanol, isopropanol and n-octanol; AgNWs@ZIF8 is dissolved in an organic solvent, and during the grinding process, the organic solvent solution of AgNWs@ZIF8 is dropped into an organic solvent containing thiourea, the mixture is heated in a water bath, and then vacuum dried at room temperature, and after the reaction is completed, it is cooled to room temperature to obtain AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials.
[0008] Preferably, the molar ratio of the cobalt salt or zinc salt to 2-methylimidazole is 1:1 to 1:20; and the mass ratio of the AgNWs@ZIF8 to urea is 1:250.
[0009] Preferably, the heating rate is 1-20°C / min.
[0010] Preferably, the concentration of the organic amine in the aqueous solution or organic solvent solution containing the organic amine is 8-9%.
[0011] Preferably, the stirring is carried out at room temperature for 1 to 48 hours and the mixture is allowed to stand for 1 to 48 hours.
[0012] Preferably, the water bath is heated to 40-80° C. and maintained for 1-12 hours.
[0013] Preferably, the cobalt salt is selected from any one or more of CdI2, CdCl2, CdBr2, CdAc2, Cd(SO4)2 and Cd(NO3)2; the zinc salt is selected from any one or more of ZnI2, ZnCl2, ZnBr2, ZnAc2, Zn(SO4)2 and Zn(NO3)2.
[0014] Preferably, after the solid-liquid separation, the solid is dispersed with alcohols, and then solid-liquid separation is performed to remove unreacted substances.
[0015] Another object of the present invention is to provide AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials prepared by the method.
[0016] Another object of the present invention is to provide the application of the AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials in photocatalytic uranyl reduction, i.e., uranium extraction from seawater.
[0017] The AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials and their preparation and application have the following advantages:
[0018] (1) The present invention uses AgNWs@ZIF8 with a high specific surface area and relatively inexpensive urea as precursors to prepare AgNWs@CdZnS2@Cd and Zn-ZIF-8 core-shell structures, which have excellent uranyl reduction ability;
[0019] (2) By controlling the molar ratio of cadmium salt to solvent, the molar ratio of zinc salt to solvent, and the molar ratio of AgNWs to cadmium salt and zinc salt solvent during the reaction process, the size of CdZnS2 and the mass ratio of AgNWs to CdZnS2 can be controlled. The preparation process parameters are easy to control, the preparation method is simple, highly controllable, and has a high yield.
[0020] (3) The AgNWs@CdZnS2@Cd and Zn-ZIF-8 core-shell structure photocatalytic materials obtained by the present invention have a large specific surface area and a wide visible light absorption, and can be used in the fields of photocatalytic uranyl reduction, i.e. uranium extraction from seawater, photocatalytic degradation, photocatalytic hydrogen production or solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The XRD spectra of the photocatalytic materials prepared in Example 1, Comparative Example 1 and Comparative Example 4 of the present invention are shown.
[0022] Figure 2 This is a scanning electron microscope image of the photocatalytic material prepared in Example 1 of the present invention.
[0023] Figure 3 The UV-visible absorption spectra of the photocatalytic materials prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention.
[0024] Figure 4 The photocatalytic reduction effect diagram of uranyl by the photocatalytic materials prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A method for preparing AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials is as follows:
[0028] (1) Preparation of Zn 2+ 、Cd 2+ and 2-MIM precursor solution
[0029] 0.01 mol C4H6O4Zn·2H2O, 0.01 mol Cd(NO3)2·4H2O and 0.2 mol 2-methylimidazole (2-MIM) were dissolved in 250 mL methanol (MeOH), 250 mL MeOH and 108.75 mL methanol solution containing 8.75% TEA (triethylamine) to form clear solutions, respectively. Zn 2+ Precursor solution, Cd 2+ Precursor solution and 2-MIM precursor solution.
[0030] (2) Preparation of AgNWs@ZIF8 powder
[0031] Under continuous stirring, 1-500 μL of AgNWs was dispersed into the 2-MIM precursor solution and poured into the Zn 2+ Precursor solution and Cd 2+ The mixed solution of the precursor solution was stirred for 2 h, then allowed to stand at room temperature for 2 h, and the yellow solid was collected by centrifugation and redispersed with methanol to remove unreacted ions and ligands. After the above dispersion-centrifugation procedure was repeated 3 times, the collected samples were dried under vacuum at 60 °C to obtain AgNWs@ZIF8 powder.
[0032] (3) Preparation of AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials
[0033] 1 g of thiourea was ultrasonically dissolved in 20-100 mL of MeOH, and the solution was shaken to disperse the AgNWs@ZIF8 powder, and then a rotor was added, sealed, heated and stirred in a 60 °C water bath for 6 hours, and then centrifuged and dried to obtain AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials.
[0034] Examples 2 and 3
[0035] It is basically the same as Example 1, except that in step (2), the AgNW contents of Examples 2 and 3 are different.
[0036] Comparative Example 1
[0037] A method for preparing AgNWs photocatalytic material is as follows:
[0038] 1 to 500 μL of AgNWs were dried in an oven at 60° C. for 6 h, cooled naturally to room temperature, and the powders were collected and ground to obtain AgNWs photocatalytic materials.
[0039] Comparative Example 2
[0040] A method for preparing a CdZnS2 photocatalytic material is as follows:
[0041] (1) Preparation of Zn 2+ 、Cd 2+ and 2-MIM precursor solution
[0042] 0.02 mol C4H6O4Zn·2H2O, 0.02 mol Cd(NO3)2·4H2O and 0.2 mol 2-methylimidazole (2-MIM) were dissolved in 250 mL methanol (MeOH), 250 mL MeOH and 108.75 mL methanol solution containing 8.75% TEA (triethylamine) to form clear solutions, respectively. Zn 2+ Precursor solution, Cd 2+ Precursor solution and 2-MIM precursor solution.
[0043] (2) Preparation of CdZnS2 powder
[0044] Under continuous stirring, pour the 2-MIM precursor solution into the Zn 2+ Precursor solution and Cd 2+ The mixed solution of the precursor solution was stirred for 2 h, then allowed to stand at room temperature for 2 h, and the yellow solid was collected by centrifugation and redispersed with methanol to remove unreacted ions and ligands. After the above dispersion-centrifugation procedure was repeated 3 times, the collected sample was dried under vacuum at 60 ° C to obtain CdZnS2 powder.
[0045] (3) Preparation of CdZnS2 photocatalytic materials
[0046] 1 g of thiourea was ultrasonically dissolved in 20-100 mL of MeOH, and the CdZnS2 powder was dispersed by shaking with this solution. Then, a rotor was added, sealed, heated and stirred in a 60°C water bath for 6 hours, and then centrifuged and dried to obtain the CdZnS2 photocatalytic material.
[0047] Comparative Example 3
[0048] A method for preparing a physical mixed material of AgNWs and CdZnS2 is as follows:
[0049] The AgNWs photocatalytic material and the CdZnS2 photocatalytic material in Comparative Example 1 and Example 2 were dried and ground together to obtain a physical mixed photocatalytic material of AgNWs and CdZnS2.
[0050] like Figure 1 Shown are the XRD patterns of the photocatalysts prepared in Example 1, Comparative Example 1 and Comparative Example 4 of the present invention, where the horizontal axis is the diffraction angle and the vertical axis is the relative intensity. It can be seen from the figure that the prepared AgNWs@CdZnS2@Cd and Zn-ZIF-8 are solid solutions (cubic structures) rather than mixtures. Comparative Example 1 is the diffraction peak of CdZnS2, corresponding to the 111, 220, and 311 crystal planes of CdZnS2, respectively. Comparative Example 4 is the peak value of Example 1 when sulfurization is complete, and the 111, 220, and 311 crystal planes of CdZnS2 can be clearly seen.
[0051] like Figure 2 As shown, it is the SEM picture of the centrifuged sample after uranyl reduction of Example 1 of the present invention and Example 1. It can be seen from the figure that Figure 2 a shows that AgNWs@CdZnS2@Cd and Zn-ZIF-8 are core-shell structures with AgNWs as core and CdZnS2 as shell. Figure 2 This core-shell structure is more clearly visible in b.
[0052] Experimental Example 1 Photocatalytic uranyl reduction
[0053] The photocatalytic uranyl reduction experiment was carried out under the irradiation of a 300W xenon lamp (CEL-PF300-T8E) using a 420nm cutoff filter. The specific process is as follows:
[0054] Disperse 20 mg of photocatalyst (photocatalytic material prepared in each embodiment or comparative example) in 50 mL of 200 mg / L UO2(NO3)2·6H2O aqueous solution, pass 25°C condensed water to simulate seawater temperature and avoid heat generated by light to volatilize the liquid. After stirring in the dark for 1 hour, light is exposed for a period of time to allow it to react fully. The initial uranyl concentration is recorded as C0, and an appropriate amount of sample is taken out at intervals. The uranyl concentration at this time is recorded as C. Use a 0.22 μm filter to filter the photocatalyst, use azobenzene colorimetric method to color the sample, and finally use UV-vis absorption spectroscopy to detect the residual uranyl concentration in the sample to evaluate the reducing ability of the catalyst.
[0055] like Figure 3As shown in a, it is the ultraviolet-visible light absorption spectrum of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-3 of the present invention, wherein the horizontal axis is the wavelength and the vertical axis is the relative absorption intensity. It can be seen from the figure that the absorption capacity of the photocatalytic material (AgNWs) prepared in Comparative Example 1 to uranyl is basically the same as the absorption capacity of the photocatalytic material (physical mixture of AgNWs and CdZnS2) prepared in Comparative Example 3 to uranyl, and the absorption of uranyl by the photocatalytic material (AgNWs@CdZnS2@Cd, Zn-ZIF-8) prepared in Example 1 is significantly stronger than that of Comparative Examples 1-3. Figure 3 As shown in FIG. 2 , it is the ultraviolet-visible light absorption spectrum of the photocatalytic materials prepared in comparative example 1 and examples 1-3 of the present invention, wherein the abscissa is the wavelength and the ordinate is the relative absorption intensity. It can be seen from the figure that the photocatalytic material (AgNWs@CdZnS2@Cd, Zn-ZIF-8) prepared in example 1 has a significantly stronger absorption capacity for uranyl than the other three, and the absorption capacity of the photocatalytic materials in examples 2 and 3 for uranyl is basically the same.
[0056] like Figure 4 As shown in a, it is a photocatalytic reduction effect diagram of uranyl by photocatalytic materials prepared by comparative example 1 and examples 1-3 of the present invention, wherein the ordinate C / C0 represents the ratio of the residual concentration to the initial concentration, which effectively reflects the ability of the catalyst to reduce uranyl. The left side of 0 is the dark reaction, and the right side is the light reaction. It can be seen from the figure that the reduction rate of uranyl in example 1 reaches 91.3%, the reduction rate of uranyl in example 2 is 71.0%, the reduction rate of uranyl in example 3 is 78.0%, and the reduction rate of uranyl in comparative example 1 is 53.2%. Figure 4 As shown in FIG. 2 , it is a photocatalytic reduction effect diagram of the photocatalytic materials prepared in Comparative Example 1 and Examples 1-3 of the present invention, wherein the ordinate C / C0 represents the ratio of the residual concentration to the initial concentration, which effectively reflects the ability of the catalyst to reduce uranyl. The left side of C0 is the dark reaction, and the right side is the light reaction. It can be seen from the figure that the reduction rate of uranyl in Comparative Example 1 reaches 53.2%, the reduction rate of uranyl in Comparative Example 2 is -4.3%, the reduction rate of uranyl in Comparative Example 3 is 63%, the reduction rate of uranyl in Comparative Example 4 is 15.9%, and the reduction rate of uranyl in Example 1 reaches 91.3%.
[0057] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 core-shell structure photocatalytic materials, characterized in that: The method includes: Propylene glycol containing PVP was placed in a bottle and heated in an oil bath with magnetic stirring. Then NaCl was quickly added and stirred continuously, followed by the addition of AgNO3 solution, and the mixed solution was heated with magnetic stirring. The precipitate was collected and washed with acetone and ethanol, respectively, to obtain gray AgNWs. 2-Methylimidazole is dissolved in an organic solvent solution containing an organic amine, AgNWs are mixed therein, and then added to an organic solvent solution of a cadmium salt and a zinc salt, stirred at room temperature, allowed to stand, and solid-liquid separated to obtain AgNWs@ZIF8; wherein the organic amine is selected from any one of triethylamine, ethylenediamine and n-butylamine; wherein the organic solvent is selected from any one of methanol, ethanol, isopropanol and n-octanol; AgNWs@ZIF8 is placed in an organic solvent, and during the grinding process, the organic solvent solution of AgNWs@ZIF8 is dropped into an organic solvent containing thiourea. The mixture is heated in a water bath and then vacuum dried at room temperature. After the reaction is completed, it is cooled to room temperature to obtain AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic material.
2. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: The molar ratio of the cadmium salt to the zinc salt and 2-methylimidazole is 1:1 to 1:20; the mass ratio of the AgNWs@ZIF8 to urea is 1:
250.
3. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: The heating rate is 1-20°C / min.
4. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: In the aqueous solution or organic solvent solution containing organic amine, the concentration of the organic amine is 8-9%.
5. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: The mixture is stirred at room temperature for 1 to 48 hours and allowed to stand for 1 to 48 hours.
6. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: The water bath is heated to 40-80° C. and maintained for 1-12 hours.
7. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to claim 1, characterized in that: The cadmium salt is selected from any one or more of CdI2, CdCl2, CdBr2, CdAc2, Cd(SO4)2 and Cd(NO3)2; the zinc salt is selected from any one or more of ZnI2, ZnCl2, ZnBr2, ZnAc2, Zn(SO4)2 and Zn(NO3)2.
8. The method for preparing AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials according to any one of claims 1 to 7, characterized in that: After the solid-liquid separation, methanol is used to disperse the solid, and then solid-liquid separation is performed to remove unreacted substances.
9. AgNWs@CdZnS2@Cd, Zn-ZIF-8 photocatalytic materials prepared by the method according to any one of claims 1 to 8.
10. Use of the AgNWs@CdZnS2@Cd and Zn-ZIF-8 photocatalytic materials as claimed in claim 9 in extracting uranium from seawater.
Citation Information
Cited By
Preparation of UiO-66-NH2 (at) CdZnS2 (at) Cd, Zn-ZIF-8 composite structure photocatalytic material and application of extraction and removal of uranium in solution
CN120361950A
Application of molybdenum disulfide-based piezoelectric catalytic material in extraction of uranium from seawater
CN121422990A